Relationship between land use type and bacterial composition in adjacent streams and riparian zones - Javad Sadeghi; Shayenna Nolan; Patricia Voyer; Zeena Biro; Yasmin Ismail; Emma Mineau; Gina Peters; Alyssa Frazao; Emily Browne; Lauren Weller; Catherine M. Febria; Terrence H. Bell; et al. (PLoS ONE, 2026)
Anthropogenic activities can negatively impact riparian and stream ecosystems, resulting in declines in biodiversity and certain ecosystem functions. Microbiomes in these environments play crucial roles in primary production, nutrient cycling, and maintaining air, soil, and water quality. While previous studies have examined the effects of land use on streams and soil microbiota, few have evaluated the effects of soil microbiota on aquatic ecosystems based on land use in the riparian systems. In this study, we characterized bacterial composition in six small to moderate-sized streams in both urban and agricultural land use areas using 16S rRNA gene amplicon sequencing and related this to measured physicochemical variables in these environments. Bacterial composition was comparable in soil samples collected at 3m and 1m from the river and in edge and sediment samples, but these differed significantly from bacterial composition in adjacent water. Bacterial alpha diversity (Shannon index) in streams was higher when adjacent to agricultural sites than urban sites, but no effect of land use type on bacterial alpha diversity was observed in soil samples. On the other hand, land use and location had significant impacts on bacterial composition in both soil and water samples. Furthermore, in our sampling sites, stream bacterial composition in agricultural sites was significantly influenced by NH 3 and NO 3 -NO 2 concentrations. These findings raise the possibility that aquatic bacterial function may be modified/influenced even when adjacent soil microbiomes appear relatively unaffected. Moreover, given the sensitivity of the water microbiota to land use variation, our results suggest that aquatic bacterial composition and diversity can serve as a powerful bioindicator for assessing riparian impacts on ecosystem health.